Astronet - Alexander, Goldie; Falla, Dominique (Macmillan Education Australia South Melbourne, Vic., 1996)
Astronet by Goldie Alexander is an engaging children's novel that follows a group of young friends who embark on an exciting adventure involving space exploration and discovery. When they stumble upon a mysterious communication device, they are drawn into a world of science, technology, and interstellar intrigue. As they decode messages and encounter challenges, the friends learn about teamwork, perseverance, and the wonders of the universe. With a blend of humor and excitement, the story encourages young readers to explore their curiosity about space and science while delivering important lessons about friendship and collaboration.